Pleasure and Addiction - Kennett, Jeanette M.; Matthews, Steve; Snoek, Anke (Frontiers in Psychiatry, 2013)
What is the role and value of pleasure in addiction? Foddy and Savulescu (1) have claimed that substance use is just pleasure-oriented behavior. They describe addiction as “strong appetites toward pleasure” and argue that addicts suffer in significant part because of strong social and moral disapproval of lives dominated by pleasure seeking. But such lives, they claim, can be autonomous and rational. The view they offer is largely in line with the choice model and opposed to a disease model of addiction. Foddy and Savulescu are sceptical of self-reports that emphasize the ill effects of addiction such as loss of family and possessions, or that claim an absence of pleasure after tolerance sets in. Such reports they think are shaped by social stigma which makes available a limited set of socially approved addiction narratives. We will not question the claim that a life devoted to pleasure can be autonomously chosen. Nor do we question the claim that the social stigma attached to the use of certain drugs increases the harm suffered by the user. However our interviews with addicts (as philosophers rather than health professionals or peers) reveal a genuinely ambivalent and complex relationship between addiction, value, and pleasure. Our subjects did not shy away from discussing pleasure and its role in use. But though they usually valued the pleasurable properties of substances, and this played that did not mean that they valued an addictive life. Our interviews distinguished changing attitudes towards drug related pleasures across the course of substance use, including diminishing pleasure from use over time and increasing resentment at the effects of substance use on other valued activities. In this paper we consider the implications of what drug users say about pleasure and value over the course of addiction for models of addiction.